The Contribution of Environmental, Social, and Governance (ESG) Disclosure to Reduce Investor Asymmetry Information - Nurunnisa Ayung Prinika Sugianto; Carissa Nariswari Riandy; Shafa Fadia Zainavy; Annisa Ilma Hartikasari (UM Purwokerto Press, 2022)
The aim of this study is to determine whether environmental, social, and governance (ESG) disclosures have an effect on reducing information asymmetry between managers and stock market participants. This study tries to provide a comprehensive analysis of the company's ESG disclosure strategy. The data used in this study were collected from companies listed on the ESG Sector Leaders BEI KEHATI (ESGSKEHATI) and ESG Quality 45 IDX KEHATI (ESGQKEHATI). The findings show that ESG disclosure reduces stock market asymmetry. From these results, ESG disclosure strengthens the informativeness of environmental disclosures for the stock market. Stakeholders must assess and maintain an increased flow of information, a more efficient disclosure strategy becomes essential if companies are to convey a true picture of their ESG performance. The concept of company development in increasing ESG can be done through maintaining the surrounding environment, sustainable development, and establishing governance. The role of the company is also important, for example by maintaining good relations with employees, suppliers, consumers, shareholders, and various organizations or individuals who interact with the company.